2007
DOI: 10.1007/s12026-007-0013-3
|View full text |Cite
|
Sign up to set email alerts
|

Chimerism and tetragametic chimerism in humans: implications in autoimmunity, allorecognition and tolerance

Abstract: The presence of cells or tissues from two individuals, chimeras, or the presence of cells and tissues that include the gonads, tetragametic chimerism can be detected by the analysis of cytogenetics and analysis of polymorphic genetic markers, using patterns of pedigree inheritance. These methodologies include determination of sex chromosomes, major histocompatibility complex (MHC) polymorphisms and panels of short tandem repeats (STRs) that include mitochondrial DNA markers. Studies routinely involve cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 127 publications
0
16
0
Order By: Relevance
“…A disadvantage is the low concentration of analytes (67 ). The advantage of extracting DNA from saliva is that the germline DNA represents only the DNA from the person who donated, compared to DNA derived from blood which could originate from other persons, such as in cases of multiple transfusions or chimerism after bone marrow transplantation (68,69 ). Furthermore, salivary DNA is a useful source of germline DNA in studies of hematologic neoplasias (70 ).…”
Section: Salivamentioning
confidence: 99%
“…A disadvantage is the low concentration of analytes (67 ). The advantage of extracting DNA from saliva is that the germline DNA represents only the DNA from the person who donated, compared to DNA derived from blood which could originate from other persons, such as in cases of multiple transfusions or chimerism after bone marrow transplantation (68,69 ). Furthermore, salivary DNA is a useful source of germline DNA in studies of hematologic neoplasias (70 ).…”
Section: Salivamentioning
confidence: 99%
“…In particular, the use of in vitro fertilisation for assisted conception, in which more than one embryo is transferred, has resulted in an increase in the number of chimaeras arising from the aggregation of embryos (Quintero et al, 2003;Souter et al, 2003). In many cases, chimaerism results from the transportation of cells between individuals via the shared circulating blood and involves organs with a good blood supply (van Dijk et al, 1996); in some instances, it extends to the germ cells (van Dijk et al, 1996;Yunis et al, 2007).…”
Section: Assessing Developmental Potential: Merging and Splitting Embmentioning
confidence: 99%
“…In particular, the use of in vitro fertilisation for assisted conception, in which more than one embryo is transferred, has resulted in an increase in the number of chimaeras arising from the aggregation of embryos (Quintero et al, 2003;Souter et al, 2003). In many cases, chimaerism results from the transportation of cells between individuals via the shared circulating blood and involves organs with a good blood supply (van Dijk et al, 1996); in some instances, it extends to the germ cells (van Dijk et al, 1996;Yunis et al, 2007).Murine chimaeras have been generated by the aggregation of embryos (Tarkowski, 1961;Mintz, 1962; Gardner, 1968; Gardner and Munro, 1974). This technique, when performed with embryos of different genotypes, has become a useful experimental device for generating mosaics and allows studies of gene function by creating organisms with cells of different genotypes (Fig.…”
mentioning
confidence: 99%
“…Immune response to collagen VII V Pendaries et al Immune response to collagen VII V Pendaries et al mother to the fetus across the placenta, 32 and chimerism between dizygotic twins has been shown. 33 Recent experiments have shown that the mammalian fetus can develop antibody responses to antigenic stimuli.…”
mentioning
confidence: 99%